A cross-cultural analysis of spiritual transcendence and its impact on job satisfaction, job security, and life satisfaction in Bali and Türkiye: mediator effect of earthquake anxiety - Subawa, Nyoman Sri; Baykal, Elif; Basmantra, Ida Nyoman; Mimaki, Caren Angellina; Yorulmaz, Halil (Frontiers in Psychology, 2024)
Earthquakes are considered as a major factor causing have been linked to PTSD, anxiety, and depression across various age groups. Increased anxiety stemming from earthquakes may prompt individuals to turn to spirituality as a coping mechanism, with spiritual transcendence believed to be an effective way to mitigate help manage and reduce anxiety. In this study, Bali, which has a Far Eastern spiritual tradition, and Turkey, the majority of whose population is Muslim, are discussed comparatively. In fact, the underlying reason for this choice is to examine whether there is a difference between Hindu belief, one of the Far Eastern religions as a spiritual tradition, and Islam, one of the monotheistic religions, regarding individuals' ability to manage anxiety and some basic psychological reactions to the fear of earthquakes. An example of Bali's Hindu tradition has been considered a representation of the Islamic tradition, one of the monotheistic religions in Turkey. Bali, renowned for its spiritual energy, and Turkey, with its Islamic heritage, provide insights into how spirituality influences coping with seismic fears. Given this phenomenon, the study took a quantitative approach, giving a novel conceptual framework for understanding the relationship between spiritual transcendence, seismic fear, job satisfaction, job security, life satisfaction, and the moderating influence of optimism. Empirical data were acquired via surveys issued via Google Form to a total of 913 workers in Bali and Turkey. The research data were analyzed using SmartPLS software and a structural equation modeling technique. Findings indicate that earthquake anxiety and the impact of spiritual transcendence on satisfaction and job security are stronger in Bali than in Turkey. Additionally, spirituality holds greater significance for the Balinese sample compared to the Turkish sample. The study clarifies the implications of its findings and provides guidance for future research endeavors.